Effect of season, genotype and lactation on milk yield and composition of local and crossbred dairy cows reared under different feed base region (Bangladesh Journal of Livestock Research, 2016)
A total of 160 cows, 10 cows in each of native (local cow) and crossbred (local × Holstein Friesian) origins differing in lactation were used in 2×2×2×2 factorial experiment using Randomized Block Design (RBD) to evaluate milk yield and composition of cows considering regions (good & poor feed base region), seasons (dry: Nov.Feb. 2009 & wet: Jun.Oct. 2009), genotypes and lactation. A good and/or poor feed base region was classified based on the availability of quantity and quality roughages throughout the year. The study revealed that the daily milk yield and 4% FCM of cows under good feed base condition were 6.76 and 6.49 kg, respectively and under poor feed base condition were 3.67 and 3.31 kg, respectively. Feed base region did not affect on milk fat and it was observed that the milk protein, lactose, solids-not-fat (SNF), minerals and total solids under good feed base condition were 37.9, 54.9, 100.9, 6.3 and 140.6 g/kg, respectively, whereas, under poor feed base condition the values were 36.3, 52.9, 98.0, 6.1 and 135.2 g/kg, respectively. Season did not affect milk yield and composition except minerals (6.5 g/kg vs. 5.9 g/kg). Genotypes significantly (p?0.01) influenced daily milk yield, the milk protein and minerals. Lactation did not affect milk yield and the milk protein, but influenced the fat, lactose, SNF, minerals and total solids. The interaction of feed base regions and seasons significantly (p?0.01) influenced milk yield and the milk fat and SNF. The milk protein and lactose was influenced by the interaction of feed bases region, seasons and lactation. Milk yield negatively correlated with fat per cent. The percentage of fat significantly (p?0.01) correlated with protein, lactose, SNF, and minerals %. The percentage protein correlated with lactose, SNF and minerals. Lactose % significantly (p?0.01) correlated with SNF%. It may be concluded that milk yield and composition depends on feed base region, genotype and lactation of cows. Season did not influence milk yield and the composition. Milk yield negatively correlated with the percentage of fat, protein, lactose, SNF and milk composition strongly correlated with each other.Bangladesh J. of Livestock Res. 19(1-2): 50-65, Jan-Dec 2012